Implementasi Internet Of Thing Sebagai Interface menggunakan Mikrokontroller Arduino Pada Alat Pendeteksi Tingkat Stress - Raja Gabe Lumban Siantar; Insani Abdi Bangsa; Reni Rahmadewi (Peneliti.net, 2021)
The more andvanced civilization, humanity pay more attention to various factors that can affect productivity level nad the quality of an operation. Not only caringto work safety but also the influence from working set-up, level of welfare, work shift’s, and work targets can affect productivity level of worker. In fact, it is not easy to determine the conditions each worker accurately, apart from the possibility of enforcing conditions but also because the distance between field workers and guarantor. In order for this to realized, tools that can simplifies process of cheking process even in the conditions that not allow face to face. As a developing technology, Internet of Things (IoT) system can facilitate access to electronic devices via internet, which in this case can allow data retrieval when conditions of limited time and long distances. With using Blynk as the fundamental for system of Stress Level Detector (Stredec), by using NodeMCU ESP8266 platform is integrated with Arduino Uno R3 and four sensors to take the stress level determining variabels, that is GSR sensor, temperature sensor, heart rate sensor, and blood pressure sensor and connected to Wi-Fi and get displayed to smartphone and LCD on device.